2023
DOI: 10.1200/jco.2023.41.4_suppl.tps765
|View full text |Cite
|
Sign up to set email alerts
|

A phase I, first-in-human, open-label, dose escalation and expansion study of PT886 in adult patients with advanced gastric, gastroesophageal junction, and pancreatic adenocarcinomas.

Abstract: TPS765 Background: PT886 is a novel bispecific antibody that targets Claudin 18.2 (CLDN18.2) and CD47. CLDN18.2 is overexpressed in a significant proportion of gastric and pancreatic adenocarcinomas and its restricted expression makes it a promising therapeutic target for the treatment of these carcinomas. Moreover, studies have found that immunoglobulin superfamily CD47 is overexpressed widely across tumor types, and CD47 plays an important role in suppressing phagocytes activity through binding to the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…CLDN18.2 is overexpressed in the majority of gastric adenocarcinomas and pancreatic cancers. Antibodies targeting CLDN18.2 could redirect macrophage-mediated phagocytic activity towards tumor cells, thereby enhancing anti-tumor activity ( 24 ). Our study also confirmed the role of CLDN18 in regulating ADCP in LIHC, underscoring the validity and potential translational value of our research.…”
Section: Discussionmentioning
confidence: 99%
“…CLDN18.2 is overexpressed in the majority of gastric adenocarcinomas and pancreatic cancers. Antibodies targeting CLDN18.2 could redirect macrophage-mediated phagocytic activity towards tumor cells, thereby enhancing anti-tumor activity ( 24 ). Our study also confirmed the role of CLDN18 in regulating ADCP in LIHC, underscoring the validity and potential translational value of our research.…”
Section: Discussionmentioning
confidence: 99%
“…A humanized immunoglobulin G1 monoclonal antibody against CLDN18.2 and an anti-CLDN18.2 antibody-drug conjugate have also shown promising antitumor activity and acceptable safety profiles in early phase studies of patients with gastrointestinal cancers ( 29, 30 ). Studies assessing safety and antitumor activity of a novel bispecific antibody against CLDN18.2 and a novel CLDN18.2-targeted CAR-T therapy in patients with solid tumors, including gastrointestinal tumors, are underway ( 31, 32 ). These therapeutic strategies have the potential to enhance the treatment landscape for patients with CLDN18.2-positive gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CLDN18.2 will remain a target of interest for further drug development and is currently undergoing many exploration trials [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Additional CLDN18.2 monoclonal antibodies are under investigation in solid tumor trials, including AB011, MIL93, and TST001 (osemitamab) [29][30][31][32].…”
Section: Future Directionsmentioning
confidence: 99%
“…For those with CLDN18.2-positive GAC and GEJ patients, ORR was 75%, with a disease control rate of 100%. PT886, a bispecific antibody that targets CLDN18.2 CD47, is under phase 1 investigation for advanced GAC, GEJ, and pancreatic adenocarcinoma patients [34]. Additionally, CLDN18.2 is under investigation as a potential chimeric antigen receptor T (CART) therapy with NCT03874897, NCT05277987, NCT04404595, and NCT03159819; its potential is currently being explored in CLDN18.2-positive patients [24][25][26][27].…”
Section: Future Directionsmentioning
confidence: 99%